2015
DOI: 10.1016/j.neuint.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of JM-20 on the glutamatergic system in synaptic vesicles, synaptosomes and neural cells cultured from rat brain

Abstract: JM-20 (3-ethoxycarbonyl-2-methyl-4-(2-nitrophenyl)-4,11-dihydro-1H-pyrido[2,3-b][1,5]benzodiazepine) is a novel benzodiazepine dihydropyridine hybrid molecule, which has been shown to be a neuroprotective agent in brain disorders involving glutamate receptors. However, the effect of JM-20 on the functionality of the glutamatergic system has not been investigated. In this study, by using different in vitro preparations, we investigated the effects of JM-20 on (i) rat brain synaptic vesicles (L-[(3)H]-glutamate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…Synaptosome preparations were obtained from the brains of Gcdh −/− and Gcdh +/+ mice as described previously . One aliquot was used immediately for neurotransmitter release assay and the other was stored in −20°C for Western blot analysis.…”
Section: Materials and Methods (For Full Methods See Data )mentioning
confidence: 99%
“…Synaptosome preparations were obtained from the brains of Gcdh −/− and Gcdh +/+ mice as described previously . One aliquot was used immediately for neurotransmitter release assay and the other was stored in −20°C for Western blot analysis.…”
Section: Materials and Methods (For Full Methods See Data )mentioning
confidence: 99%
“…In addition, the long-term therapeutic effect of this compound suggests its ability to modulate synaptic plasticity. Considering that glutamatergic neurotransmission plays a pivotal role in central sensitization that occurs in NP, the regulatory effect of JM-20 on the glutamate homeostasis could be involved in this phenomenon (Latremoliere and Woolf, 2009;Nuñez-Figueredo et al, 2015). In line with these ideas, the downregulation of glutamate transporters in the spinal cord to the paclitaxel-induced hyperalgesia has been reported (Weng et al, 2005).…”
Section: Discussionmentioning
confidence: 86%
“…This paper showed that the treatment with JM-20 prevented the increase of the expression of pro-apoptotic signaling proteins, protecting neuronal loss and presumably cognitive impairment, and in this line of findings the authors suggested that JM-20 may prevent memory impairment via mitochondrial protection and the inhibition of the intrinsic apoptosis pathway, also suggesting a therapeutic benefit to neurodegenerative dementia like Alzheimer’s disease. The results on the regional effects of transient cerebral ischemia on astrocytes reactivity and the PI3K/Akt survival pathway, and the role of JM-20, were shown by Ramírez-Sánchez Jeney [ 50 , 51 ].…”
Section: Lecture Highlightsmentioning
confidence: 99%